(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Understanding peace cultures, edited by Rebecca L. Oxford, a volume in the series: Peace Education, editors Laura Finley & Robin Cooper, Information Age Publishing, 2014, 344 pp., US 45.99 (paperback), US 85.99 (hardcover), ISBN 978-1-62396-505-1.